Test loan loss provisioning hypotheses for Chinese bank from 2011 to 2016 - Cheng, Haonan (2017)
Abstract The object of this dissertation is to investigate the loan loss provision behavior in Chinese bank from 2011 to 2016.This research is based on corresponding empirical literatures and 92 banks (includes: commercial and saving banks) in China. two models are used in this research, which is Stochastic frontier analysis and Generalized method of moments. X-efficiency is contained in this dissertation and the estimation variables of loan loss provision are estimated by GMM model. The consequence in this research strongly supports the pro-cyclical provision behavior in Chinese banking system. However, there is no significant variables sustain the capital management and earning management hypotheses in China banking system. Keywords: Loan loss provision; Chinese bank; X-efficiency; GMM model; pro-cyclical provision behavior